Political Interviews with Donald Trump: Uncovering Power and Context through Critical Political Discourse Analysis - Xu, Xu; Ballena, Constantino T. (Philippine Social Science Journal, 2022)
The study explored the CPDA framework in analyzing political interviews, particularly with President Donald Trump on the US trade war with China. The study mainly explored how political power was revealed in political interviews with President Trump and what these political interviews revealed about the contexts of President Trump. The corpus constituted ten political interview episodes coded as PIE1, PIE2, and so forth with an average length of 11minutes 26 seconds. The results revealed political power in the political interviews with President Trump as evidenced by his unusually loud volume, unusually low pitch, and falling intonation of expression structures and his positive evaluation of US or Our action and negative evaluation of Them or Their action as underpinned by semantic polarization. Moreover, ideological polarization, rhetoric, and practical argumentation uncovered President Trump’s context of "America First" thought, his hegemony, high extraversion, low agreeableness, domestic high opposition to his trade war against China, and populism. Finally, the procedures in undertaking CPDA could be utilized by researchers in their analysis of political speeches and interviews to uncover notions of power and contexts.